Influence of multiple global change drivers on plant invasion: Additive effects are uncommon - Yang, Bin; Cui, MiaoMiao; Du, YiZhou; Ren, GuangQian; Li, Jian; Wang, CongYan; Li, GuanLin; Dai, ZhiCong; Rutherford, Susan; Wan, Justin S. H.; Du, DaoLin (Frontiers in Plant Science, 2022)
Invasive plants threaten biodiversity and cause huge economic losses. It is thought that global change factors (GCFs) associated with climate change including shifts in temperature, precipitation, nitrogen, and atmospheric CO2 will amplify their impacts. However, only few studies assess mixed factors on plant invasion. We collated the literature on plant responses to GCFs to explore independent, combined, and interactive effects on performance and competitiveness of native and invasive plants. From 176 plant species, our results showed that: (1) when native and invasive plants are affected by both independent and multiple GCFs, there is a positive effect on plant performance, but a negative effect on plant competitiveness; (2) under GCFs such as increased precipitation or combined with temperature, most invasive plants gain advantages over native plants; and (3) interactions between GCFs on plant performance and competitiveness are synergistic or antagonistic. Our results indicate that native and invasive plants will be affected by independent or combined GCFs, and invasive plants will gain advantages over native plants. The interactive effects of factors on plants are non-additive, but the advantages of invasive plants may not increase indefinitely. Our findings show that inferring the impacts of climate change on plant invasion from factors individually could be misleading. More mixed factor studies are needed to predict plant invasions under global change.